Homework Help

How do you factorize? (x-3)^2 - (x+4)^2

tamanim's profile pic

Posted via web

dislike 2 like

How do you factorize?

(x-3)^2 - (x+4)^2

1 Answer | Add Yours

jeew-m's profile pic

Posted (Answer #1)

dislike 2 like

We know that;

`A^2-B^2 = (A+B)(A-B)`



`A = (x-3)`

`B = (x+4)`



`= A^2-B^2`

`= (A+B)(A-B)`

`= (x-3+x+4)(x-3-(x+4))`

`= (2x+1)(-7)`

`= -7(2x+1)`


So the answer is;

`(x-3)^2-(x+4)^2 = -7(2x+1)`

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes